Padrões espaciais na distribuição de espécies de Cichlidae (Percomorpha) no Estado do Maranhão, avaliando o compartilhamento de fauna com três Ecorregiões Neotropicais de Água Doce - CAMPOS, Diego Sousa (2016)
We seek to gather information about the diversity of cichlids present in three ecoregions in the transition between the Amazon area, the Northeast and the Midwest of Brazil, and also spatial patterns in the distribution and occurrence of species, with comments on species richness patterns and species sharing. We used occurrence data from 82 species of cichlids in 69 watersheds included in three eco-regions: the Amazon Estuary and Coastal Drainages (EADC), Tocantins-Araguaia (TA) and Parnaíba (PI); covering an area of approximately 1.7 million square kilometers. Species richness and distribution patterns were compared between watersheds and ecoregions. The variables of bioclimatic were calculated from coordinates of the occurrence of the species and were used to describe the environment. Our analysis indicated a pattern of greater richness of cichlid species in the ecoregion of the EADC, followed by TA basins and PI. The largest share of EADC and TA was found, with 50 species in common, while these two ecoregions share only 13 species each with ecoregion Parnaíba and only 11 species were common to the three ecoregions. The most species focuses drains below 250m in ecoregions EADC and PI, while in the TA region to extend well above 500m. Temperature and rainfall showed inverse relationship with elevation and latitude, while the annual temperature range was directly related. Despite the large number of species accumulated in the three ecoregions studied sharing between the three is relatively low, although EADC and TA present several species in common. Environmental characteristics such as temperature and annual rainfall were associated with elevation, the same pattern observed the relief configuration represented the main divide in the distribution of species with almost all of the species found below 250m. But as few samples were taken above this elevation in ecoregions EADC and Parnaíba, this could be indicative that the headwaters of rivers in these regions should receive more attention in the search for undetermined species.